Prasangka Keagamaan dalam Komunikasi Antarumat Beragama Hindu Islam di Puja Mandala Nusa Dua Bali - Najikh, Ahmad Hayyan; Syah, Farhan Walid Syah (Icon: Islamic Communication and Contemporary Media Studies, 2024)
This study examines the importance of social interaction in human life, especially interactions supported by religion, and how tolerance forms within a diverse society. Tolerance, naturally developed by humans, is defined as the disposition to permit differences in beliefs and behaviors. This research focuses on the dynamics of religious tolerance at Puja Mandala in Nusa Dua, Bali, emphasizing the communication interactions between Hindu and Muslim communities living side by side. Using a qualitative approach, the researcher observes the circular communication pattern (Circular Pattern) and the star pattern (Star Pattern), where each group member has an equal opportunity to participate. These patterns allow for the observation of how messages are conveyed, received, and how communication flows in balanced situations. The findings show that tolerance practices at Puja Mandala involve respect for other religions' beliefs and rituals, orderliness in worship practices, and acceptance of individual differences. Factors such as cultural background and personal experience play a role in shaping positive communication that supports tolerant behavior. The study concludes that tolerance can be achieved through effective communication patterns, fostering interfaith harmony. The implications of this research aim to contribute to the strengthening of tolerance and social harmony values within Indonesian society.